Primary hyperparathyroidism: A clinicopathological experience - Sathe Pragati; Madiwale Chitra; Kandalkar Bhuvaneshwari; Bandgar Tushar; Shah Nalini; Menon Padma (Wolters Kluwer Medknow Publications, 2009)
Background: Parathyroid neoplasms form a small percentage of head and neck neoplasms. Primary hyperparathyroidism is caused by parathyroid adenomas, hyperplasia or, rarely, a carcinoma. Materials and Methods: This is a retrospective study of 48 parathyroidectomies received in the Department of Pathology of a major teaching hospital over a period of 10 years. Clinical, biochemical and radiological details were retrieved from medical records. Information regarding routine gross and microscopic examination findings (including frozen section and paraffin sections) was retrieved from departmental records. Results: We had 43 adenomas, three hyperplasias and two carcinomas. The most common age group was 21-30 years. The female:male ratio was 2.5:1. Most patients presented with skeletal manifestations. The pre-operative diagnosis was assisted by ultrasonography in 11 cases, computerized tomography of the neck in 10 cases and sestamibi scans in three cases. Intra-operative parathormone monitoring was performed in one case of adenoma. Frozen section was requested in 28 of 48 cases. There was a discrepancy between frozen section diagnosis and paraffin section diagnosis in two cases. Conclusion: Histopathologic diagnosis is an important guide to decide the type of surgical management. Although pathologic features of parathyroid carcinoma are diagnostically reliable, those of the more commonly encountered lesions of adenoma and hyperplasia may be overlapping and, therefore, indistinctive, more so if only a single gland is available for examination. Because parathyroid lesions are only occasionally encountered by the surgical pathologist, awareness of the spectrum of histologic features along with knowledge of recent trends in diagnosis and surgical management are important.